Chronic Recurrent Multifocal Osteomyelitis in Pediatric Crohn Disease, A Paradoxical Effect to Antitumor Necrosis Factor Alpha. Issue 2 (20th November 2020) - Cordesse, Anne; Ecochard-Dugelay, Emmanuelle; Melki, Isabelle; Caseris, Marion; Belarbi, Nadia; Hugot, Jean-Pierre; Viala, Jerome; Martinez-Vinson, Christine
Abstract : Tumor necrosis factor-α (TNF-α) inhibitors have resulted in significant progress in the treatment of chronic inflammatory diseases. However, these therapies can lead to paradoxical immune-mediated inflammatory diseases with unknown physiopathology. For the first time, we report 3 cases of paradoxical chronic recurrent multifocal osteomyelitis after infliximab or adalimumab therapy during the course of Crohn disease. The patients complained of bone pain without joint involvement. At the time of diagnosis of paradoxical reaction, all patients were in remission due to anti-TNFα efficiency. Trough levels of anti-TNFα were in the expected range, and there were no anti–anti-TNFα antibodies. The duration of treatment was between 2 and 26 months. Other causes of CRMO were excluded. All patients recovered after discontinuation of infliximab (n = 2) or adalimumab (n = 1). The increasing use of these therapies leads to new descriptions of paradoxical effects, which clinicians should be aware of.